Evaluation of Hospital Mesra 'Ibadah (HMI) program in government and private hospitals in the Klang Valley - Noor Azizah Tahir
This research sought to examine the process of Islamicisation in Malaysian medical field. It studied the Hospital Mesra ʻIbadah (HMI) program. Its objectives were to identify a framework that are been embedded in HMI in terms of its dimensions, current status and activities as well as to study the correlations amongst Subjective Knowledge (SK), Objective Knowledge (OK), the variables of Attitude (A), Subjective Norms (SN) Perceived Behavioural Control (PBC) and Behavioural Intention (BI) . It utilised an Exploratory Sequential Design of Mixed Method Research. A total of 39 participants were recruited using the snowballing theoretical sampling technique in its qualitative phase that involved 10 In-Depth Interviews (IDIs) and 7 Focus Group Discussions (FGDs) during its first two qualitative phase. Data were transcribed and analysed using the NVivo software. The analyses identified a conceptual framework that consists of 4 dimensional nodes namely aspects, facets, domains and areas. One of the areas that is on providing spiritual support was identified as a relevant dimension from this phase and therefore, was chosen to be focused in the subsequent quantitative phase. The subsequent quantitative phase utilised three sets of questionnaires that were developed and validated during the research in order to study some correlations amongst Subjective Knowledge (SK), Objective Knowledge (OK), the variables of Attitude (A), Subjective Norms (SN) Perceived Behavioural Control (PBC) and Behavioural Intention (BI). A total of 540 respondents were recruited from Hospital Putrajaya and Hospital Sungai Buloh to validate the 75-items-questionnaires (QSK4-QOK15-QTPB-56 HMI Questionnaires). A final validated 43-items-questionnaires (QSK2-QOK8-QTPB-33 HMI Questionnaires) was generated and utilised in the subsequent quantitative phase which was the correlation study in the action of giving spiritual supportive advice to patients. During this third phase, 35 respondents were recruited from Hospital Al-Islam and 50 random respondents were selected from Hospital Putrajaya and Hospital Sg Buloh. Data was analysed using IBM SPSS Statistic 22 software. The identified dimensions produced the aforementioned framework of HMI program called Primordial HMI Conceptual Framework. It found that there were 10 PBC factors controlling the performance of staff in giving spiritual support to patients. These were patient's misunderstanding about the intention of the staff in giving advice, lonely patient, egoistic patient, patient's emotional readiness, patient with illness involving ablution body parts, perception towards patient's family as own, experience superiors, lack of counselling skills, lack of staffing and time constraint. It found that the awareness about the HMI program varied amongst the staff. There were inverse correlations between both the SK and A as well as SK and PBC and moderate correlations between A and BI as well as between PBC and BI with no significant difference in the correlations between government and private hospitals. The inverse relationships between SK and A and SK and PBC suggested that instilling confidence in HMI is evidence based as it will overcome A and PBC factors. The 3 sets of validated questionnaires and the Primordial HMI Conceptual Framework from this research could be used for further development of theory and practice of HMI.